The Landbound Chicken and the Deliberate Chameleon yet have their Uses: Yorùbá Art History, Language, and Interpretation. - Kathy Curnow (Yoruba Studies Review)
Rowland Abiodun’s Yorùbá Art and Language contains many extremely valuable features, wrapped around a question he raises in its introduction: can foreign scholars ever truly understand a work the way its Yorùbá makers and users do? Language mastery certainly provides the native speaker with access to inestimable insights regarding not only general worldview, but specifics of philosophy, history keeping, and subtleties of knowledge transmission. However, in the attempt to read an artwork and unpack its meaning, cultural in[1]siders also face obstacles as well as advantages, particularly when pieces date from the more distant past. The import of Abiodun’s major contributions regarding Yorùbá art’s history and the validity of his contentions are considered here in light of the varied contributions both foreign and Yorùbá art historians bring to Yorùbá scholarship, in the recognition that working with art of bygone centuries makes all scholars outsiders to a degree.